2005
DOI: 10.2166/wst.2005.0534
|View full text |Cite
|
Sign up to set email alerts
|

A low-cost municipal sewage treatment system witha combination of UASB and the “fourth-generation”downflow hanging sponge reactors

Abstract: This paper presents an evaluation of the process performance of a pilot-scale "fourth generation" downflow hanging sponge (DHS) post-treatment system combined with a UASB pretreatment unit treating municipal wastewater. After the successful operation of the second- and third-generation DHS reactors, the fourth-generation DHS reactor was developed to overcome a few shortcomings of its predecessors. This reactor was designed to further enhance the treatment efficiency and simplify the construction process in rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 0 publications
4
33
0
3
Order By: Relevance
“…The profile analysis of the wastewater stream along the height of the G3-DHS bioreactor treating desluging septic tank wastewater showed that soluble COD (organic substance) and ammonia were removed mainly in the upper portion (Figure 2). This finding has also similar presented by other studies [7], [6], [9], [14]. It could be implied that the microenvironment almost certainly differs along the bioreactor height.…”
Section: Performances Of G3-dhs Bioreactorsupporting
confidence: 90%
See 1 more Smart Citation
“…The profile analysis of the wastewater stream along the height of the G3-DHS bioreactor treating desluging septic tank wastewater showed that soluble COD (organic substance) and ammonia were removed mainly in the upper portion (Figure 2). This finding has also similar presented by other studies [7], [6], [9], [14]. It could be implied that the microenvironment almost certainly differs along the bioreactor height.…”
Section: Performances Of G3-dhs Bioreactorsupporting
confidence: 90%
“…The principal objective of this research is to evaluate the performance of the thirdgeneration of downflow hanging sponge (G3-DHS) bioreactor for treatment of desludging wastewater from IPTL. DHS bioreactor was originally published in 1997 by Machdar et al [5] and has been explored for extensive time by numerous researchers [6], [7], [8], [9], [10], [11], [12] for treatment of domestic wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Much of SS was entrapped in the fiber module and provided a long SRT. The performance was similar to that of the cube-type or the curtain-type DHS reactor (Machdar, 1997, Machdar, 2000, Tandukar et al, 2005. Time course of unfiltered COD and typical DO profile along the PF-DHS reactor height are shown in Fig.…”
Section: Pf-dhs Reactor Process Performancementioning
confidence: 54%
“…One of the most important factors for aerobic reactors to achieve a good performance in treatment process is the DO concentration. DHS reactor has an advantage of needlessness of external aeration although being an aerobic system (Machdar et al, 1997;Tandukar et al, 2005Tandukar et al, , 2006. The DO level of effluent from the PF-DHS pilot plant was all the time kept around 6.3 mg/L (SD ± 0.8 mg/L) although the DO was 2.1 mg/L (SD ± 0.6 mg/L) at the inlet.…”
Section: Pf-dhs Reactor Process Performancementioning
confidence: 99%
See 1 more Smart Citation